Analysis of patients' and health care providers' perceptions on the delivery of quality health care services at a tertiary medical center in Quezon City - Santella-Jara, Margarita S.
This is a qualitative descriptive study on perceptions of customers and health care providers quality of health care provided by the different service areas of a tertiary training hospital . Two groups of respondents consisted of 2256 customers and 61 health care providers. Satisfaction on the different dimensions of care such as promptness of service, competency, clarity of explanation by the personnel, attentiveness, courtesy and compassion of the staff, condition of apparatus, instruments and facilities and amenities were evaluated. A Likert scale was used to obtain the degree of satisfaction of the services. The dimension of care with excellent satisfaction among the patients were attentiveness, courtesy and compassion of the staff with a mean rating of 4.21 while the least satisfaction is with the amenities with a mean of 4.07. The health care providers were also most satisfied with attentiveness, courtesy and compassion of the staff with a mean of 3.9 while least satisfied with the condition of the apparatus, instruments and facilities with a mean of 3.30. On the perception of the different health care services as a whole, there exists a significant difference between the two study populations on interpersonal relationship and clarity of explanation. Overall, patients were most satisfied with the medical and nursing services and least satisfied with the admitting and discharge or business office. Health care providers on the other hand were most satisfied with Security, Admitting, Emergency Room, Dietary and Housekeeping Services areas and with lesser satisfaction with Radiology, Nursing and the Laboratory. There was a significant difference on the delivery of quality care service between the two population groups in the nursing, laboratory, dietary, emergency, radiology and discharge or business office.